The Effect of Compensation and Work Motivation on Employee Performance at PT. Anugerah Riau Mustika - Sahlan, Sahlan; Susilowati, Yuli; Arta Mevia, Dilla (Lafadz Jaya Publisher, 2022)
The purpose of this study is to determine the effect of compensation and work motivation on employee performance at PT Anugerah Riau Mustika. This research was conducted from September 2021 to April 2022 at PT Anugerah Riau Mustika which is located on Jalan Paus No. 127 Pekanbaru. The target of this study is employees at PT Anugerah Riau Mustika who are still working in 2022. The population in this study was 52, to determine the sample used the slovin technique with a sample of 34. Data obtained from through the distribution of questionnaires. The analysis methods used are validity test, reliability test, analysis of multiple linear regression equations, classical assumption test, t test, F test, and coefficient of determination using the SPSS (Statistics Product Service and Solution) program version 20.0. Based on the hypothesis and analysis of the research results, it can be concluded that compensation has a partial effect on the performance of employees of PT Anugerah Riau Mustika. Work motivation does not have a partial effect on the performance of employees of PT Anugerah Riau Mustika. Compensation and work motivation have a simultaneous effect on the performance of employees at PT Anugerah Riau Mustika. Compensation and work motivation contributed 50.2% to employee performance at PT Anugerah Riau Mustika, while the rest were outside the regression equation or variables that were not studied in this study.